Swine Acute Diarrhea Syndrome Coronavirus: An Overview of Virus Structure and Virus–Host Interactions - Seung-Hwa Baek; Jung-Eun Park (Animals)
SADS-CoV, a recently identified Rhinolophus bat coronavirus HKU2-associated swine coronavirus, is a malignant pathogen that causes acute diarrhea, severe diarrhea, and weight loss in infected piglets. The virus was first detected in Guangdong Province, China, in 2017 and has since been observed in Jiangxi, Fujian, and Guangxi Provinces. In 2023, the virus was detected in Henan Province, in inland China. This virus can infect various cell lines, including human cell lines, showing significant potential for cross-species transmission and posing a possible zoonotic threat. However, the molecular biology of SADS-CoV remains largely unknown, and there are no commercially available therapeutics or vaccines to prevent SADS-CoV infection. In this review, an update on progress in SADS-CoV research is provided, with a focus on the history of outbreaks, the characteristics of the virus, its interactions with the host, and developments in therapeutics and vaccines.